The EU 2020 Innovation Indicator: A step forward in measuring innovation outputs and outcomes? - Jürgen Janger; Torben Schubert; Petra Andries; Christian Rammer; Machteld Hoskens (Austrian Institute of Economic Research (WIFO), 2016)
In October 2013, the European Commission presented a new indicator intended to capture innovation outputs and outcomes and thereby "support policy-makers in establishing new or reinforced actions to remove bottlenecks that prevent innovators from translating ideas into products and services that can be successful on the market". This paper aims to evaluate the usefulness of the new indicator against the background of the difficulties in measuring innovation outputs and outcomes. We develop a unique conceptual framework for measuring innovation outcomes that distinguishes structural change and structural upgrading as two key dimensions in both manufacturing and services. We conclude that the new indicator is biased towards a somewhat narrowly defined "high-tech" understanding of innovation outcomes. We illustrate our framework proposing a broader set of outcome indicators capturing also structural upgrading. We find that the results for the modified indicator differ substantially for a number of countries, with potentially wide-ranging consequences for innovation and industrial policies.
Keywords: O25; O31; O38; O52; 330; Innovation Output; Innovation Outcome; Innovation Measurement; Structural Change; Structural Upgrading; EU 2020 Strategy; Innovation Policy